Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.<br